Correction of a Class III Angle malocclusion in an adult patient with the Edgewise Archwire Multiloop technique with a 1-year post-treatment control - Valdez Galdos, Mariana (2020)
The treatment of compensation or camouflage of Class III malocclusions was traditionally oriented to the extraction of first lower premolars, canine distalization and lingualization of lower incisors in order to obtain an acceptable overbite and overjet. The purpose of this report is to describe the diagnosis and treatment plan of a Class III malocclusion in an adult patient, supported by a literature review. The case was treated with the Multiloop Edgewise Arch Wire (MEAW) system and lower third molars were extracted. The MEAW system uses arches with loops placed in the interproximal dental spaces, from the distal part of the lateral incisors to the last tooth in the posterior area, to which certain activations are performed according to the malocclusion. It can be concluded that with this system the compensation of Class III cases is possible through the reconstruction of the occlusal plane and avoiding the extraction of lower premolars. Also, controlling the lingualization effect of the lower incisors a correct overjet and overbite and Class I canine relations can be achieved.